Characterization of antioxidant activity of exopolysaccharides from endophytic Lysinibacillus sphaericus Ya6 under osmotic stress conditions. (February 2022) - Yang, Fengrui; Chen, Jiuliang; Ye, Shuhong; Liu, Zhaofang; Ding, Yan
Graphical abstract: Highlights: The exopolysaccharide (EPS) was homogenous with molecular weight of 89.62 kDa. The EPS from L. sphaericus Ya6 was composed of mannose and a small amount of glucose. Under osmotic stress, scavenging activity of EPS on DPPH radical was enhanced. All EPS samples had scavenging activity against DPPH radical and superoxide anion. Abstract: In this study, the antioxidant properties of exopolysaccharides (EPS) produced by Lysinibacillus sphaericus Ya6 under different osmotic stress were investigated. High-performance liquid chromatography was used to analyse the monosaccharide composition of EPS. High-performance gel permeation chromatography was used to determine the molecular weight of EPS. Results suggested that EPS produced by Lysinibacillus sphaericus Ya6 was a homogenous polysaccharide with molecular weight of 89.62 kDa, which was composed of mannose and glucose. The molecular weight and monosaccharide composition of polysaccharides changed under osmotic stress conditions. In vitro antioxidant determinations found that all EPS had activity of scavenging 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical and superoxide anion. And with the aggravation of osmotic stress, the scavenging activity of EPS produced by Lysinibacillus sphaericus Ya6 on DPPH radical was enhanced from 39.30 ± 0.19 % (control condition) to 72.54 ± 0.3 %.